The Role of Literature in the Processes of Destereotyping (Through Examples from Macedonian Literature) - Marija Gjorgjieva Dimova (Slavia Meridionalis, 2022)
The Role of Literature in the Processes of Destereotyping (Through Examples from Macedonian Literature)